Performances and phylogenic relationships among local sheep in Indonesia by morphological analysis - C Sumantri; A Einstiana; J.F Salamena; I Inounu (Indonesian Center for Animal Research and Development (ICARD), 2007)
The morphological discriminant and canonical analysis were carried out to estimate the phylogenic relationship and determine the discriminant variables between Indonesian local sheep of thin tail sheep from Jonggol (Bogor) and Garut and fat tail sheep from Indramayu (originated from East Java), Donggala, Madura, Kisar, Rote and Sumbawa. The number of sheep used was totally 818 heads collected from 8 populations, were Jonggol (185), Garut (74), Indramayu (100), Donggala (60), Madura (86) Kisar (231), Rote (52), and Sumbawa (30). Discriminant analysis used for body weight and body measurements were body length, wither height, chest width, chest depth, chest circumference, skull length, skull width, skull height, tail lenght, tail width, ear length and ear width. SAS package program was used to analyze the data. The results from analysis variant showed that the body weight and body measurenment of Garut sheep almost the same with sheep from Indramayu and significantly higher (P<0,05) compared to another breeds. Whereas, Kisar and Rote have body weight and body measurenment significantly lower (P<0,05) compared to another breeds. The results from Mahalanobis distance (phenogram tree) and canonical analyses showed that breeds were divided into five groups, the first group is Garut, the second is thin-tail sheep which existed in Jonggol, the third was fat-tailed sheep which existed in Kisar, Rote, and Sumbawa, the fourth is fat-tail sheep which existed in Donggala, and the fiveth was fat-tailed sheep which existed in Indramayu and Madura. The groups of sheep between Kisar and Rote had the smallest genetic distance value equal to 1,623 and groups between Donggala and Garut had the biggest genetic distance value equal to 7,994. The highest similarity between individual inside the group was obtained from Sumbawa (100%) and the lowest similarity was from Rote (72,41%). The results from canonical analyses showed that tail lenght, ear width, ear lenght, skull lenght, body lenght, and tail width were the most discriminant variables to determine the diferences between breeds. Key Words: Sheep, Genetic Distance, Analysis Discriminant and Cannonica